If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = -3 + -8 Multiply f * x fx = -3 + -8 Combine like terms: -3 + -8 = -11 fx = -11 Solving fx = -11 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -11x-1 Simplifying f = -11x-1
| 16k^2+122k=-70 | | 3X^3-X^2-30X=0 | | log(11-x)=.5 | | 8(28)= | | f(-2)=-3x-8 | | 6x-8=2x+1 | | 49+7x=21 | | 2ln(x)-ln(2x-5)=ln(7x)-ln(x+2) | | 300*.10=5 | | 10x+4-2x=8 | | 4cotx+1=5 | | 2400-160x+2x^2=1312.5 | | 7r^2+5r+3=0 | | 8s^2-22s+5=0 | | (x+0.5)(x+3.4)=0 | | 2.16b+5=1.6b+10 | | 144= | | 144=12 | | 2(2z-2)-2(4-2z)=2 | | 3x+15+39=90 | | 12r^2+3=0 | | 3x+15+39=180 | | 7x-16=-1 | | 8-3=10y | | -2x+1-(-3x+3)=-4+(-x-2) | | 0.8=0.2y+3.4 | | 5t-23=-23+7t | | 9x+19=-26 | | -3p-5-p-(-3p)+4p+7p+5= | | 4x^3-40x^2+96x=0 | | 2t-22=-16+5t | | 4x^3-9x^2+2=0 |